Constraints on green renovation of building based on the theory of whole lifecycle and green development - Qiaohui Tong; Wei Wei; Yekai Le (PLoS ONE, 2025)
Green renovation of building (GRB) is usually full of challenges and limited by multiple factors, including environment, technology, materials, and region. It is necessary to lower the impact on residents’ lives and reasonably address construction waste during the renovation process. In this study, a system dynamics model was constructed according to the whole lifecycle theory and green development theory to evaluate the comprehensive benefits of GRB. This model was adopted to analyze the constraints during the renovation process. In addition, the key indicators, were simulated, including pollution, greenness, and resident satisfaction. The system dynamics model simulation results indicated that during the decision-making and project phases, the simulated greenness value of GRB reached 1.623, with a variation value of 1.515. This finding substantiated the substantial influence of this phase on greenness transformation. During the engineering warranty and post-evaluation phase, the greenness change value was the highest of 6.173. Therefore, long-term maintenance and continuous improvement are crucial for greenness. Meanwhile, the proportion of green energy usage gradually increased during the GRB process, while other energy consumption and pollution indicators decreased. This demonstrated the potential of GRB in promoting sustainable development. The study has validated the efficacy of the simulation and analysis of GRB projects through the system dynamics method while providing theoretical foundations for the planning and implementation of GRB projects. By comprehensively considering technological, economic, policy, and social factors, system dynamics model can assist decision-makers in optimizing GRB strategies, achieving a dual improvement in environmental and economic benefits.